REPRESENTASI SEKSUALITAS PADA VIDEO KLIP ‘BLANK SPACE’ - Anna Puji Lestari (Universitas Bunda Mulia, 2017)
Song title ‘Blank Space’ singing by Taylor Swift reputed as feminis song. This research paradigm is critical. Critical theory which is used is Muted Group as grand theory and Cultural Radical Feminist as middle range theory. Data analysis technic used semiotic by Roland Barthes. The research results show that the video and the Blank Space Lyric represented woman differently. The song lirics represented power and subjectivity of woman. Vice versa, the video represented gender bias which is controlled by patriarchy and capitalism. These two ideology used sexuality only for selling as male gaze.Keyword: Blank Space, sexuality, patriarchy, exploitation.